2003
DOI: 10.1097/00002030-200311210-00019
|View full text |Cite
|
Sign up to set email alerts
|

In vitro infection of human primary adipose cells with HIV-1

Abstract: We reassessed the infection ability of human primary preadipocytes. The use of X4, R5 or VSV-G-pseudotyped viral particles indicated that viral entry is the limiting step. However, transfection with HIV-1 receptors restored efficient infection. Analyses of CD4, CXCR4 and CCR5 expression on preadipocytes and adipocytes revealed that receptor co-expression levels did not permit HIV-1 entry into adipose cells from all biopsies tested. We concluded that adipose tissue cannot be infected with HIV-1 in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 6 publications
3
23
0
Order By: Relevance
“…This result is also in agreement with previous contradicting results showing that CD4 protein can be detected in mature adipocytes [7,19] but not in biopsies [8]. We concluded that CD4 is likely to be expressed in adipose cells but at a very low level and with a great interindividual variability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is also in agreement with previous contradicting results showing that CD4 protein can be detected in mature adipocytes [7,19] but not in biopsies [8]. We concluded that CD4 is likely to be expressed in adipose cells but at a very low level and with a great interindividual variability.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Hazan and colleagues have shown that human adipose cells express all necessary HIV receptors and that adipose cells could be infected by HIV-1 in vitro [7]. However, the same authors have reassessed this result to conclude that adipose tissue cannot be infected in vitro because HIV receptor expression levels did not permit entry into adipose cells from all biopsies tested [8].…”
Section: Introductionmentioning
confidence: 99%
“…68 However, the results of further studies led to a questioning of this possibility. 69,70 More recently, it has been reported that human adipocytes in primary culture are susceptible to HIV-1 infection, and exposure to high levels of TNFa, as occurs in adipose tissue of HALS patients, leads to effective HIV-1 replication and production by adipocytes. 71 On the other hand, cellular components other than adipocytes that are present inside adipose tissue depots may also be the targets of HIV-1 infection.…”
Section: Lipomatosis In Hals Reveals a Potential For Brown Adipocyte mentioning
confidence: 99%
“…Although adipocytes may be potentially infected by HIV, there is controversial evidence [8,9]. However, indirect effects of HIV infection, even under effective ART, have been reported in lipodystrophy adipose tissue to contribute to lipodystrophy [10,11].…”
Section: Introductionmentioning
confidence: 99%